Activation of peroxymonosulfate by CoFe2O4 loaded on metal-organic framework for the degradation of organic dye. (February 2020) - Zhang, Ke; Sun, Dedong; Ma, Chun; Wang, Guanlong; Dong, Xiaoli; Zhang, Xinxin
Abstract: The magnetic composite CoFe2 O4 /ZIF-8 based on metal organic framework (MOF) with high specific surface area and high activity was synthesized by solvothermal method. The prepared catalysts were characterized by scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), vibration sample magnetometer (VSM) and N2 adsorption-desorption isotherms, respectively. After characterization, CoFe2 O4 /ZIF-8 was applied to heterogeneous activation of peroxymonosulfate (PMS) for degrading methylene blue (MB). The result showed that the 0.075-CoFe2 O4 /ZIF-8 sample had the excellent catalytic activity. After catalytic reaction for 60 min, the degradation efficiency of MB (20 mg/L) reached about 97.9% at room temperature of 20 °C. The quenching experiment and electron paramagnetic resonance (EPR) analysis indicated that SO4 − and OH radicals were the main active species in MB degradation. Meanwhile, the possible MB degradation mechanism was proposed. After four catalytic cycles, the degradation efficiency of MB has not been greatly reduced, indicating the practical application potential of CoFe2 O4 /ZIF-8 in water pollution cleanup. Graphical abstract: Image 1 Highlights: CoFe2 O4 /ZIF-8 as a catalyst was synthesized using a facile solvothermal method. CoFe2 O4 was dispersed on the surface ZIF-8 effectively. Magnetic properties of CoFe2 O4 /ZIF-8 facilitated the recovery of the catalyst. SO4 − and OH played important roles in the oxidation process of MB.